The Application of Quality Function Deployment (QFD) Method in Improving the Quality of Tape at UD. Raja Tape, Bondowoso Regency - Hasanah, Iraudatul; Wardhana, Danu Indra; Nalawati, Ara Nugrahayu (International Applied Science, 2024)
Bondowoso is the best tape-producing region in East Java, with a production of 435,969 kg in 2018 . One of the tape production centers in Bondowoso is UD. Raja Tape. This study aims to identify the quality attributes of Raja Tape products and determine the operational policies needed to improve product quality at UD. Raja Tape. The Quality Function Deployment (QFD) method is used to identify and understand customer needs and desires into relevant technical specifications for the production process. This research was conducted over three months, using primary data obtained through field observations and interviews, as well as secondary data from related literature. The research stages include identifying products and competitors, conducting product surveys to gather the voice of the customer, identifying technical parameters, analyzing the relationship between customer importance and technical parameters, and constructing the House of Quality (HoQ). The results indicate that the application of QFD can identify key areas that need improvement in the tape production process, such as raw materials, fermentation techniques, and packaging. Implementing the recommendations from the QFD results led to significant improvements in tape product quality, marked by increased customer satisfaction and reduced complaints. This study demonstrates that the QFD method can be an effective strategy for improving product quality in the traditional food industry.